The role of attachment style, attachment to therapist, and working alliance in response to psychological therapy. (11th November 2014) - Taylor, Peter J.; Rietzschel, Julia; Danquah, Adam; Berry, Katherine
<x xml:space="preserve">Abstract</x> Objectives Working alliance (WA) has been shown to be an important process influencing the success of therapy. The association of clients' underlying attachment representations with WA and the subsequent success of therapy has increasingly been recognized. This study explores the association between adult attachment representations, specific attachment to the therapist and WA in patients receiving psychological therapy. Method Fifty‐eight participants due to receive therapy were recruited from primary care psychological services. Participants completed self‐report measures of attachment, WA, and psychopathology. Results Patients with greater secure attachment to the therapist showed significantly greater WA. In a subset of participants completing therapy, change in outcome was also correlated with baseline attachment towards the therapist. Conclusions The study suggests that attachment towards the therapist is an important predictor of WA. The results suggest that in terms of WA, attachment to the therapist may be more important than pre‐existing attachment representations. Practitioner points A more secure attachment to the therapist was associated with greater WA and improvement in therapy. Clinicians should be mindful of signs of an insecure attachment to themselves, reflecting a difficulty around trusting the therapist and viewing them as a secure base. Missed sessions and an ongoing reluctance to disclose personal information to the therapist may be signs of an insecure attachment. This may be the case even in cognitive–behavioural approaches to therapy where relational processes are not necessarily a focus of therapy. Incorporating attachment processes in the formulation, including attachment to the therapist, may provide one way of exploring these issues in therapy.